Comparative Study of Numerical Analysis of Compacted Strand and Round Strand under Axial Tensile Load. (June 2022) - Zhang, Feng; Cao, Yang; Deng, Yong; Qian, Zhong; Yuan, Chunyu; Zhu, Yixian; Wu, Guoqing
Using differential geometry theory, geometric modeling and finite element modeling of round strand and compacted strand before and after the rolling process are carried out. Using Costello theory, the rationality of the model is verified. The effects of five different friction factors on the mechanical properties of both were simulated and analyzed under the same axial tensile load. The results show that under the same axial tensile load and friction factor, the maximum equivalent stress and displacement of the compacted strand is smaller than those of round strand. When the axial load is 5 kN and the friction factor is 0, the maximum equivalent stress of the compacted strand relative to the round strand is reduced by 38.1%, and the displacement is reduced by 19.3%. Under the same axial tensile load and different friction factors, the maximum equivalent stress of the round strand increases approximately linearly with the friction factor; while the maximum equivalent stress of the compacted strand has a small increase between the friction factor of 0 and 0.05, and after 0.05 the maximum equivalent stress almost does not change. The displacement of both decreases as the friction factor increases. Under the same strain, the reaction force of the compacted strand is greater than that of the round strand, which proves that the compacted strand has higher tensile strength than the round strand.